THE COMPARATIVE CHARACTERISTICS GASOLINE VOLATILITY WITH DIFFERENT CONTENT OF OXYGENATES - Нешта, М. В.; Бойченко, С. В.; Нешта, М. В. (Science-based technologies, 2014)
The influence of aliphatic alcohols on the physical stability of gasoline. The influence of oxygenates in the fractional composition of the fuel. The results of studies of the effect of isopropyl, ethyl isobutyl alcohol on performance characteristics of gasoline A-95.